Myeloperoxidase (MPO) genotype and lung cancer histologic types: The MPO −463 A allele is associated with reduced risk for small cell lung cancer in smokers - Dally, Heike; Schmezer, Peter; Spiegelhalder, Bertold; Edler, Lutz; Drings, Peter; Dienemann, Hendrik; Schulz, Volker; Kayser, Klaus; Bartsch, Helmut; Risch, Angela (International journal of cancer, 2002)
MPO participates in the metabolic activation of tobacco carcinogens such as PAHs. A frequent MPO −463 G→A polymorphism in the promoter region reduces MPO transcription and has been correlated with >4...
Gesehen am 12.01.2021